Pengembangan Modul Pembelajaran Kimia Materi Pokok Struktur Atomberbasis Inkuiri Terbimbing - Tri Saslina; Mawardi Mawardi; Latisma Dj (Journal on Education, 2021)
Type of research is the research and the development (R & D) to develop chemistry learning modules for the main material atom structural based guided inquiry and to explain about validity, practicality and effectiveness of the resulting module. Expansion model used is 4-D model. The development begins with analyze the front end, the students, the tasks and the concepts analysis. It’s be continued by designing chemistry learning modules based guided inquiry. Than the module developed through development stage such as validation and revision based on validator comments to get valid learning module to be tested in the field. The valid learning module was tested to the students to explain the module practicality and effectiveness. The result of data analysis show that learning module was valid with the average value of kappa moment 0,73. Practicality module was shown by the result of data analysis of questionnaire for teacher response with kappa moment value 0,85 and the questionnaire for student response with kappa moment 0,80. Based on the result of this study, it can be concluded that learning module was valid and practical to used in chemistry learning. The effectiveness test showed that the average value of students’ understanding was 82,31.